Study on deformation zoning of overlying strata and simulation of rock pressure behavior in longwall top coal caving mining - Xinxian ZHAI; Zhaoyang GUO; Jianchang FANG; Zhiyong ZHANG; Xiaofan ZHAO (Meitan kexue jishu)
At present, longwall top coal caving (LTCC) mining is main mining method for safety and efficiency mines with extremely-thick coal seam in China. However, the deformation movement law of overlying strata on LTCC face directly affects rock pressure behavior of LTCC face, selection of hydraulic supports, and selection of top coal caving technique and parameters, etc. Based on the engineering background on LTCC face 13200 in Gengcun Coal Mine, using similar simulation test and theoretical analysis, the paper studied the whole process of deformation, movement and caving of overlying strata, their deformation zoning, and the characteristics of rock pressure behavior of LTCC face. The results show that: ① It is determined that there are multi-layer key strata on LTCC face, i.e., the lower, middle, upper and main key strata. According to the collapse instability characteristics of key strata in different layers, the whole process of deformation movement of overlying strata on LTCC face is divided into four deformation stages. Each deformation stage is related to the collapse instability of key stratum in different layers. ② After the collapse instability of the lower key strata in LTCC mining, with the continuous increase of LTCC face advancement, the middle, upper and main key strata in the fractured zone have separated from their lower strata before the collapse instability. Before the collapse of the key strata, the collapse arch is formed in its lower strata, and the height and width of the collapse arch are positively correlated with LTCC face advancing distance. ③ The collapse instability of each key stratum on LTCC face directly causes the peak stress concentration factor Kmax of the front abutment pressure to increase. When the lower key stratum collapses and loses stability, the phenomenon of large periodic weighting occurs on LTCC face, the weighting interval is larger, but the weighting strength is lower; the collapse of the middle and upper key strata or the main key stratum will cause the lower key stratum to collapse at the same time, and the phenomenon of small periodic weighting occurs on LTCC face. The weighting interval is smaller, but the weighting strength is higher. The research conclusions provide theoretical basis and technical supporting for LTCC face with the gently-inclined and extremely-thick coal seam in Gengcun Coal Mine.